Challenging the inequities of ebike access: An investigation of a community-led intervention in a lower-income neighbourhood in Aotearoa - New Zealand - Witten K; Opit S; Mackie H; Raja A (Elsevier B.V., 2024)
Introduction Ebiking offers positive physical and mental health benefits for riders. However, inequitable access to bike share schemes and purchase cost barriers limit ebike availability and uptake in lower-income communities. Furthermore, as bike culture differs from place to place, incentive schemes responsive to the local culture are needed to improve access to ebikes as a healthy mobility choice. Methods Three trials of ebike access were co-designed sequentially between 2021 and 2023. Give-it-a go, Ebikes in daily life, Pathway to Permanence were all designed by a community bike organisation working in tandem with a research team. Trial delivery was community-led. Trial participants’ experiences of ebike use were gathered through group and individual interviews, and the research also included a brief before and after survey of trip destination and mode use. Results Trial participants valued their ebiking experience, including the skills training and group rides, new knowledge of safe routes, health benefits of exercise, and fuel savings. During the trial, a third of weekly trips were made by ebike, while trips made by motor vehicle reduced by 25%. Cost emerged as a substantial barrier to ebike ownership. Conclusions Effective models to support ebike uptake in lower-income communities will be characterised by: adequate funding of community organisations to grow local bike culture; safe and secure bike infrastructure; community ownership of an ebike fleet to support skill acquisition and social connection; and a pathway to low-cost ebike access.
Keywords: Transport inequities; Active travel; Ebikes; Health inequities; Qualitative; Community intervention